INDONESIAN CLASSROOM MANAGEMENT BY TWO NONNETIVE SPEAKER TEACHERS TO SECOND LANGUAGE LEANERS - Elfia, Elfia (Jurnal Mentari, 2012)
Laporan ini mengkaji metode-metode pengelolaan kelas oleh dua guru yang bukan berbahasa Indonesia  saat mengajar bahasa tersebut. Dalam studi ini keduanya menunjukkan kecakapan mereka dalam mengajar pelajaran bahasa Indonesia di sekolah menengah.Tujuan dari laporan ini untuk memberikan sebuah pengetahuan kepada guru bahasa asing lainnya dalam hal pengajaran bahasa di  dalam kelas bahasa kedua mareka, yaitu bahasa Indonesia. Data yang dikumpulkan untuk studi initer masuk catatan observasi, rekaman audio, dan wawancara. Analisa tersebut menyatakan bahwa peningkatan kemampuan berbaha saamat dipengaruhi oleh peran yang dimainkan guru. Untuk mewujudkan sebuah praktik berbahasa yang nyata, guru harus lebih sering menggunakan bahasa kedua dalam aktivitas kelas untuk merangsang ketertarikan siswa terhadap bahasa daripada sebaliknya yang mungkin telah mareka lakukan.     References   Allen, E. D & Valette, R. M. (1977). Classroom Techniques: Foreign Languages and English as a second language. Harcourt Brace Jovanovich. USA Chastain, K. (1988). Developing second-language skills. Theory and Practice. Harcourt Brace Jovanovich. University of Virginia Corrie, M, Haystead, J & Zaklukiewicz, S. (1982). Classroom Management strategies.London Ellis, R. (1986). Understanding second language acquisition. Oxford University Press. Oxford Gibbons, P. (2006). “A sociocultural view of language and learning”. In Bridging Discourses in the ESL Classroom: Students, teachers and researchers, (pp. 15-41). London, New York: Continuum. Halliday, M.A.K. (1978). Language and social man (part 1). In language As Social Semiotic: The Social Interpretation of Language and Meaning, (pp.8-35). London: Edward Arnold Magos, K & Politi, F. (2008). The creative second language lesson: The contribution of the role-play technique to the teaching of a second language in immigrant classes.Vol 39(1), 96-112. Retrieved October 22,2009, from Ebsco elctronic journal services (EJS) websites: http://RELC.sagepub.com Mickan, P. (2006). Socialisation, social practice and teaching. In social practices, pedagogy and language use: studies in socialisation. Eds P Mickan, I Petrescu and J Timoney. Adelaide: Lythrum Press. Thornbury, S & D. Slade. (2006). Teaching Conversation: Approach, design, procedure and process. Conversation: From Description to Pedagogy (pp.273-325). Cambridge: Cambridge University Press. Walsh, S. (2007). A framework for analysing classroom interaction. In Investigating Classroom Discourse, (pp.62-92). London, New York: Routledge Yi, F. (n. d). EFL classroom management: Creating a Positive Climate for Learning, (pp.128-137) Yoon, B. (2007). Offering or limiting opportunities: Teachers’roles and approaches to English-language learners’ participation in literacy activities. The reading teacher. 61(3), 216-225